2013
DOI: 10.1152/ajpheart.01102.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pkd2 mesenteric vessels exhibit a primary defect in endothelium-dependent vasodilatation restored by rosiglitazone

Abstract: Patients with autosomal dominant polycystic kidney disease have a high prevalence of hypertension and structural vascular abnormalities, such as intracranial aneurysms. Hypertension can develop in childhood and often precedes a significant reduction in the glomerular filtration rate. The major aim of this study was to investigate whether a primary endothelial defect or a vascular smooth muscle (VSM) defect was present in murine polycystic kidney disease (Pkd)2 heterozygous mesenteric vessels before the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Reduced anti-oxidant protection of the cysteine residue in the reactive site of DDAH can result in decreased DDAH activity and elevated circulating levels of ADMA during oxidative stress [28,29]. The link between oxidative stress and endothelial dysfunction in ADPKD is also supported by a recent experimental study [30] in mice with polycystic kidney disease 2. In that work, the acetylcholine-stimulated endothelium-dependent vasodilatation in isolated arterioles was impaired and accompanied by elevated basal superoxide and sodium nitroprusside-stimulated peroxynitrite formation in isolated vascular smooth muscle cells (VSMC), whereas these defects were reversible after the administration of the peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist rosiglitazone [30].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced anti-oxidant protection of the cysteine residue in the reactive site of DDAH can result in decreased DDAH activity and elevated circulating levels of ADMA during oxidative stress [28,29]. The link between oxidative stress and endothelial dysfunction in ADPKD is also supported by a recent experimental study [30] in mice with polycystic kidney disease 2. In that work, the acetylcholine-stimulated endothelium-dependent vasodilatation in isolated arterioles was impaired and accompanied by elevated basal superoxide and sodium nitroprusside-stimulated peroxynitrite formation in isolated vascular smooth muscle cells (VSMC), whereas these defects were reversible after the administration of the peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist rosiglitazone [30].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly lower expression of eNOS and nNOS has been shown in varicose veins as a result of chronic venous stasis, which suggested to the authors that mechanisms other than NO release should be involved in pathological dilation (8). Decreased bioavailability might contribute according to observations on mesenteric venules by Brookes et al (2), who found that increased vascular oxidative stress limited the effect of NO. The insulin resistance previously observed in PCOS (21,31) can also interfere with the NO pathway (38).…”
Section: Discussionmentioning
confidence: 93%
“…The saphenous veins were allowed to equilibrate for 30 min at 5-mmHg intraluminal pressure in an oxygenized nKR solution. After incubation, the pressure was first decreased to 2 mmHg and then increased to 20 mmHg in steps (2,4,6,8,10,15, and 20 mmHg). The steady-state diameter at each step was measured.…”
Section: Measuring the In Vitro Biomechanics And Pharmacological Reacmentioning
confidence: 99%
“…An inverse correlation between serum high-density lipoprotein levels and both the rate of kidney growth and the decline in glomerular filtration rate has been observed in ADPKD patients [30]. Furthermore, several clinical studies have demonstrated that oxidative modification of low-density lipoprotein in patients with early stage ADPKD can drive the deterioration of renal function and hypertension [31, 32]. Consequently, ADPKD patients exhibit more severe coronary lesions and more frequently undergo CABG.…”
Section: Discussionmentioning
confidence: 99%